Global cortical atrophy (GCA) associates with worse performance in the Montreal Cognitive Assessment (MoCA). A population-based study in community-dwelling elders living in rural Ecuador. Issue 1 (January 2015) - Del Brutto, Oscar H.; Mera, Robertino M.; Zambrano, Mauricio; Soriano, Francisco; Lama, Julio
Highlights The MoCA associates with severity of GCA. MoCA scores may be used as reliable estimates of structural brain damage. MoCA cut-offs for cognitive impairment should be lower in underserved populations.